3D-Printed Boron-Nitrogen Doped Carbon Electrodes for Sustainable Wastewater Treatment via MPECVD - Iwona Kaczmarzyk; Malgorzata Szopińska; Patryk Sokołowski; Simona Sabbatini; Gabriel Strugala; Jacek Ryl; Gianni Barucca; Per Falås; Robert Bogdanowicz; Mattia Pierpaoli (Nano-Micro Letters, 2025)
Highlights A novel approach combining 3D printing, phase inversion, and microwave plasma-enhanced chemical vapor deposition is presented. This technique enables the creation of carbon-based electrodes with precise micro- and nanoscale control, offering potential for sustainable and high-performance wastewater treatment applications. The synthesized 3D carbon scaffolds, enriched with B,N-doped carbon nanostructures, demonstrated superior performance in the electrochemical oxidation of β-blockers. Computational fluid dynamics simulations were used to optimize electrode design, leading to improved mass transport and reaction kinetics. This research provides a sustainable and scalable solution for removing emerging contaminants from wastewater. The catalyst-free approach simplifies the fabrication process and reduces potential material contamination, making it a promising technology for advanced water treatment applications.